Jóhann Jónsson – ein isländischer Dichter in Deutschland - Kreutzer, Gert (Folia Scandinavica Posnaniensia, 2007)
This article gives a summary of the life and the work of the Icelandic poet Johann Jonsson (1896-1932), who had lived in Leipzig since 1921 and also died there. To this end, published and unpublished letters by the poet are evaluated on a large scale. In the appendix, two of his most important works, the poem “SoknuSur” and the prose fragment “Nott i Riesental”, are presented in a German translation.